O impacto das personagens ausentes na obra de Clarice Lispector - Fazilari, Fábio Luiz (2006)
This essay aims to analyse Clarice Lispector s literary work, A Paixão Segundo G.H. and the short story, O Búfalo which is found in Laços de Família. It is intended the equalization concerning to the both of the literary works through the analyses of the secondary characters, depicting their relevance on conducing of the narrative cells. It will also be searched the role of the secondary characters in Lispector s plot, relating to the building and to the supporting of the main characters existential disagreement during the narrative course. It will be added to this work the research about some stylistic strategies applied by the writer, aiming at a harmonious uniformity argumentative, connected to a natural and creative production achieving its plenitude through an interchange between form and subject. It will also be prosecuted the dialog between literary theory and other sciences which arise in Clarice Lispector s works.